141. Rapid Reduction in Concomitant Vancomycin and Piperacillin-tazobactam Use: A Model for Future Antimicrobial Stewardship Interventions. (31st December 2020) - Kimball, Joanna; Deri, Connor; Nesbitt, Nesbitt J; Nelson, George; Staub, Milner
Abstract: Background: Concomitant vancomycin and piperacillin-tazobactam use (CVPTU) for >2 days is associated with increased nephrotoxicity. At Vanderbilt University Medical Center, a sustained decline in CVPTU was achieved. A retrospective review of CVPTU and antimicrobial stewardship (AS) interventions was performed to develop a model for future AS quality improvement (QI) initiatives. Methods: Data for adults receiving CVPTU January 2015 - August 2019 were extracted. No patients were excluded. Change in monthly incidence of CVPTU >2 days in relation to AS interventions was the primary outcome. CVPTU was analyzed with statistical process control (SPC) charts (QI Macros 2019). AS interventions were amassed from AS emails, meeting minutes, presentations and patient-specific interventions. We created a new intervention evaluation tool using the Hierarchy of Effectiveness (1-Education, 2-Policy, 3-Reminders, 4-Simplification, 5-Automation, 6-Forced Function) and a self-designed scale of impact (1-divisional subgroup, 2-division, 3-department, 4-center-wide). Scores were summed for each 6-month period and rated as low, moderate or high intervention strength. Periods were mapped against their corresponding CVPTU rate (Figure 1). Results: CVPTU Data : During periods 1–5 (January 2015 - February 2018), an average 4% of admitted patients received >2 days CVPTU, decreasing to < 1% from period 5 (March 2018) onward (Figure 1). From period 1–5, an average 52.8% of patients with CVPTU received >2 days and dropped to 41.3% from period 5 onward (Figure 2). Intervention Data : There was 1 low, 3 moderate and 4 high intensity periods. Intensity decreased as initiatives transitioned from behavior change to sustained behavior (Figure 1). The main interventions were education and patient-specific feedback. Division-specific antibiotic algorithms and computerized order sets re-enforced behavior. Infectious diseases consults and team pharmacists embedded the concept in daily practice. Figure 1: Proportion of All Admissions with Concomitant Vancomycin and Piperacillin-Tazobactam Use (CVPTU) for >2 Days Mapped Against Simultaneous Quality Improvement Interventions. Figure 2: Proportion of Patients with Concomitant Vancomycin and Piperacillin-Tazobactam Use (CVPTU) for >2 Days. Conclusion: Persistent, repetitive center-wide intervention is key to driving and sustaining change. More analysis of specific intervention types and impact of external factors would enhance understanding and future use of this AS change implementation model. Disclosures: All Authors : No reported disclosures